Pengaruh penerapan teknologi vakum dan non-vakum terhadap umur simpan pangan berminyak - Isananto Winursito; Arum Yuniari (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2005)
Research about the application of vaccum and non vacuum technology for the storage of greasy food using two types of polyethylene (0. Mm) and bilayer (polyethylene and nylon 0.09 mm) was carried out. The objective of the research was to know the influence of packaging for technology storage of greasy foods (sambel pecel). The result showed that water vapour permeability of bilayer was lower than of polyethylene and the score was 1.72 mg/24 hours for polyethylene and 1.58 mg/24 hours bilayer. Water activity (aw) after 60 days storage was 0.43-0.56. while the score of peroxide value of greasy foods packed using non vacuum technology was 10.18-24.98 mg Fe2+ and the score of greasy foods (sambel pecel) using vacuum technology was 10.18-17.48 mg Fe2+ and the score of greasy foods (sambel pecel) using vacuum technology was 10.18-17.48 mg Fe2. Sensories evaluation of greasy foods indicated with bilayer and vacuum technology gave high score. Key words: greasy food, vacuum, non vacuum, polyethylene, bilayer plastic. ABSTRAKPenelitian mengenai penerapan teknologi vakum dan non vakum terhadap umur simpan pangan berminyak (sambel pecel) menggunakan bahan polietilen (0,1 mm) dan bilayer (0,09 mm). tujuan penelitian ini untuk mengetahui pengaruh teknologi pengemasan terhadap umur simpan pangan berminyak (sambel pecel). Hasil penelitian menunjukkan bahwa permeabilitas terhadap uap air bilayer lebih rendah dari polietilen dan nilainya adalah polietilen 1,72 mg/24 jam dan bilayer 1,58 mg/24 jam. Aktivitas air setelah disimpan 60 hari adalah 0,43-0,56. Nilai peroksida dari sambel pecel yang dikemas non vakum adalah 10,18-24,98 mg Fe2 dan untuk vakum 10,18-17,48 mg Fe2. Hasil evaluasi uji sensoris menunjukkan bahwa sambel pecel yang dikemas dengan bilayer dan vakum teknologi memperoleh nilai tinggi.Kata kunci: sambel pecel, vakum, non vakum, polietilen, plastic dua lapis.